Nexuses between Food, Energy, and Water Consumption on Urban-Rural Income Gap in South-Eastern Asian Countries Using Difference in Difference in Modelling Technique - Khamjalas, Khambai (International Journal of Economics and Financial Issues, 2024)
South Asian countries are still battling hunger and poverty, especially in rural areas. Empirical evidence attributes the urban-rural income gap to inadequate infrastructure, such as electricity and water supply. This article uses a difference-in-difference model to examine how emerging trends in Food, Energy, and Water (FEW) resources influence the urban-rural income gap. Using data from 2000 to 2019 from China, Indonesia, and India, the results showed that high food insecurity increases income inequality, whereas electricity supply significantly reduces the income gap. Thus, Asians should ensure a sustainable and equitable distribution of FEW resources to improve agricultural productivity and create jobs.